2014
DOI: 10.1039/c4cp02253j
|View full text |Cite
|
Sign up to set email alerts
|

On the scaling behavior of electric conductivity in [C4mim][NTf2]

Abstract: In this work we examine, for the first time, the molar conductivity behavior of the deeply supercooled room temperature ionic liquid [C4mim][NTf2] in the temperature, pressure and volume thermodynamic space in terms of density scaling (TV(γ))(-1) combined with the equation of state (EOS). The exponent γσ determined from the Avramov model analysis is compared with the coefficient obtained from the viscosity studies carried out at moderate temperatures. Therefore, the experimental results presented herein provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 50 publications
4
29
2
Order By: Relevance
“…4,8,29,40 14,15,29,17,214 Additionally, pρT data of [C4C1im][NTf2], 218 [C6C1im][NTf2], 207 The pressure dependencies of the density and heat capacity, isentropic compressibility, the isothermal compressibility, isobaric expansibility, isochoric thermal-pressure coefficient, isochoric heat capacity are calculated by acoustic method using the well-known thermodynamic relationships. 8,14,15,29 214 are in a very good agreement with data obtained by high pressure densimeter 14,17,207,218,286 , while a bad agreement with the high-pressure specific volumes obtained using dilatometer 287 17 and with excellent agreement with calculated by the acoustic method by Gomes de Azevedo et al 14 (the maximum deviation is 0.0013 GPa -1 at 10 MPa and 303.15 K). Herein, a statistical analysis is presented in Table 5.…”
Section: Calculation Of Volumetric Properties and Thermodynamic Formasupporting
confidence: 75%
See 1 more Smart Citation
“…4,8,29,40 14,15,29,17,214 Additionally, pρT data of [C4C1im][NTf2], 218 [C6C1im][NTf2], 207 The pressure dependencies of the density and heat capacity, isentropic compressibility, the isothermal compressibility, isobaric expansibility, isochoric thermal-pressure coefficient, isochoric heat capacity are calculated by acoustic method using the well-known thermodynamic relationships. 8,14,15,29 214 are in a very good agreement with data obtained by high pressure densimeter 14,17,207,218,286 , while a bad agreement with the high-pressure specific volumes obtained using dilatometer 287 17 and with excellent agreement with calculated by the acoustic method by Gomes de Azevedo et al 14 (the maximum deviation is 0.0013 GPa -1 at 10 MPa and 303.15 K). Herein, a statistical analysis is presented in Table 5.…”
Section: Calculation Of Volumetric Properties and Thermodynamic Formasupporting
confidence: 75%
“…where N is the number of points of the data set considered. y1 -data reported by Dzida et al 214 , y2 -data reported by b Esperança et al 17 , c Gomes de Azevedo et al 14 , d Hamidova et al 218 , e Currás et al 286 , f Wojnarowska et al 287 and g Safarov et al 207…”
Section: Calculation Of Volumetric Properties and Thermodynamic Formamentioning
confidence: 94%
“…(9) in Ref. 35) with the values of its fitting parameters earlier reported for PVAc, 35 BMPC, 36 KDE,37 BmimNTf2, 38 TEAC, 27 and determined herein 39 for TBAC. The total system entropy S has been calculated from the well-known thermodynamic formula,…”
mentioning
confidence: 73%
“…As a result, the difference in transport properties between PILs and AILs can be suitably resolved. 32 at ambient and elevated pressure (up to 600 MPa) using dielectric spectroscopy. This technique probes molecular fluctuations and measures the dielectric/electrical response over many orders of magnitude in frequency and in a wide temperature and pressure interval, proving to be the ideal experimental tool for this quest.…”
Section: Introductionmentioning
confidence: 99%